Cytotoxic, Anti-Hemolytic, and Antioxidant Activities of Ruta chalepensis L. (Rutaceae) Extract, Fractions, and Isolated Compounds - Joel H. Elizondo-Luévano; Nancy E. Rodríguez-Garza; Aldo F. Bazaldúa-Rodríguez; César I. Romo-Sáenz; Patricia Tamez-Guerra; María J. Verde-Star; Ricardo Gomez-Flores; Ramiro Quintanilla-Licea (Plants, 2023)
Ruta chalepensis is an herb used to treat various ailments, and its potential cytotoxic effects on different tumor cell lines have been extensively studied. The present study aimed to evaluate the cytotoxic activity of R. chalepensis methanol extract (RCME), sub-partitions obtained from solvents of increasing polarity, and major compounds, as well as their hemolytic, anti-hemolytic, and antioxidant potential. The in vitro cytotoxic activity against the human hepatocarcinoma (HEP-G2) and the murine lymphoma cell line (L5178Y-R) was evaluated using the colorimetric 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay, whereas selectivity indices (SIs) were determined by comparing cytotoxicity against normal African green monkey kidney cells (VERO) and human peripheral blood mononuclear cells (PBMC). Hemolytic and anti-hemolytic activities were evaluated on human erythrocytes. The most effective cytotoxic treatment was evaluated for nitric oxide release by J774A.1 macrophages. Antioxidant activity of R. chalepensis material was also determined. Results showed that RCME produced significant (p < 0.05) cytotoxicity in HEP-G2 (IC50 = 1.79 µg/mL) and L5178Y-R (IC50 = 1.60 µg/mL) cells and exhibited high SIs (291.50 and 114.80, respectively). In addition, the n-hexane fraction (RCHF) showed an IC50 of 18.31 µg/mL in HEP-G2 cells and an SI of 9.48 in VERO cells, whereas the chloroform fraction (RCCF) evidenced an IC50 of 1.60 µg/mL in L5178Y-R cells and an SI of 34.27 in PBMC cells. Chalepensin (CHL), rutamarin (RTM), and graveolin (GRV), which are major components of R. chalepensis, showed high activity against L5178Y-R cells, with IC50 of 9.15, 15.13 and SI of 45.08 µg/mL, respectively. In addition, CHL, RTM, and GRV showed SIs of 24.76, 9.98, and 3.52, respectively, when compared with PBMC cells. RCME at concentrations of 125 µg/mL and 250 µg/mL, significantly (p < 0.05) decreased nitrite production in J774A.1 cells, when exposed to lipopolysaccharide. This study demonstrated that RCME showed significant cytotoxic activity against HEP-G2 and L5178Y-R cells, without affecting normal VERO, PBMC, and J774A.1 cells.